Investment in the commons: Lessons learned from the Mayan Biosphere Reserve, Guatemala - Monterroso, Iliana (2018)
Iliana Monterroso POLICY SEMINAR The Future of the Commons Co-organized by IFPRI, the International Association for the Study of the Commons (IASC), and the CGIAR Research Program on Policies, Institutions, and Markets (PIM)